64CuS‐labeled nanoparticles: a new sentinel‐lymph‐node‐mapping agent for PET–CT and photoacoustic tomography. (15th August 2016) - Liu, Qiufang; Zhou, Min; Li, Panli; Ku, Geng; Huang, Gang; Li, Chun; Song, Shaoli
Abstract : Determining sentinel lymph node (SLN) status is critical to cancer staging and treatment decisions. Currently, in clinical practice, 99m Tc‐radiocolloid‐mediated planar scintigraphy and single‐photon emission computed tomography (SPECT) are used to guide the biopsy and resection of SLNs. Recently, an emerging technique that combines positron emission tomography (PET) and photoacoustic tomography (PAT; PET–PAT) may offer accurate information in detecting SLNs. Herein, we report a kind of 64 CuS‐labeled nanoparticle ( 64 CuS‐NP) for the detection of SLNs with PET–PAT. We subcutaneously injected 64 CuS‐NPs into the rats' forepaw pads. After 24 h, the rats' first draining axillary lymph nodes (i.e. the SLNs) could be clearly visualized with micro‐PET (μPET)–CT. Rats were sacrificed after μPET–CT imaging, their axillary lymph nodes were surgically identified, and then PAT was employed to discover 64 CuS‐NP‐avid SLNs, which were embedded inside tissues. Biodistribution, autoradiography, and copper staining analyses confirmed the SLNs' high uptake of 64 CuS‐NPs. Our study indicates that 64 CuS‐NPs are a promising dual‐function agent for both PET–CT and PAT and could be used with multi‐modal imaging strategies such as PET–PAT to identify SLNs in a clinical setting. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : 64 CuS‐NPs, which had excellent retention in the sentinel lymph nodes (SLNs) after subcutaneous injection, could serve as a promising dual‐function agent for both PET–CT and PAT, and our study provides groundwork for employing a multimodal imaging strategy to image SLNs in a clinical setting.